Barbed Wire University : the untold story of the interned Jewish intellectuals who turned an island prison into the most remarkable school in the world /: the untold story of the interned Jewish intellectuals who turned an island prison into the most remarkable school in the world. (2021) - Hannigan, Dave
No abstract available